2021
DOI: 10.1016/j.ebiom.2021.103230
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 persistence is associated with antigen-specific CD8 T-cell responses

Abstract: Background: Upon SARS-CoV-2 infection, most individuals develop neutralizing antibodies and T-cell immunity. However, some individuals reportedly remain SARS-CoV-2 PCR positive by pharyngeal swabs weeks after recovery. Whether viral RNA in these persistent carriers is contagious and stimulates SARS-CoV-2-specific immune responses is unknown. Methods: This cohort study was conducted between April 3 rd ÀJuly 9 th 2020, recruiting COVID-19 recovered individuals that were symptom-free for at least 14 days. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
145
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 44 publications
(57 reference statements)
2
145
1
5
Order By: Relevance
“…With this approach, we detected viral RNA from the sequential sampling events of two infected cats (TAMU-013 and 057) at least three weeks after their initial positive tests. Prolonged duration of PCR-positivity has also been observed in pharyngeal swabs from post-symptomatic humans recovered from COVID-19 [ 35 ]. In that study, although the observed ongoing cellular anti-SARS-CoV-2 response is indicative of persistent viral replication, the studied human cases were not associated with any transmission to close contacts, leading to the interpretation that persistent PCR positive individuals are not contagious [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach, we detected viral RNA from the sequential sampling events of two infected cats (TAMU-013 and 057) at least three weeks after their initial positive tests. Prolonged duration of PCR-positivity has also been observed in pharyngeal swabs from post-symptomatic humans recovered from COVID-19 [ 35 ]. In that study, although the observed ongoing cellular anti-SARS-CoV-2 response is indicative of persistent viral replication, the studied human cases were not associated with any transmission to close contacts, leading to the interpretation that persistent PCR positive individuals are not contagious [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged duration of PCR-positivity has also been observed in pharyngeal swabs from post-symptomatic humans recovered from COVID-19 [ 35 ]. In that study, although the observed ongoing cellular anti-SARS-CoV-2 response is indicative of persistent viral replication, the studied human cases were not associated with any transmission to close contacts, leading to the interpretation that persistent PCR positive individuals are not contagious [ 35 ]. Further, persistent infections have been reported for other coronavirus infections, and the role of persistent infection with SARS-CoV-2 in animals is yet to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…If this phenotype exists at all, it is likely that such people are in the minority. Interestingly, there is emerging evidence in favour of an association between the T-cell response and positive PCR testing weeks following recovery from infection 59 , as this model would predict.…”
Section: Routes To Resistancementioning
confidence: 79%
“…Persistence has been widely documented in COVID-19, characterized by extensive lung thrombosis, long-term persistence of viral RNA in pneumocytes and endothelial cells, along with the presence of infected cell syncytia [24]. This feature has been mainly reported in patients with impaired immunity or cancer around the globe [25,26]. However, information of SARS-CoV-2 persistence using whole-genome sequencing is scarce, with only one case of follow-up in an immunocompromised patient [27].…”
Section: Discussionmentioning
confidence: 99%